Systematic Review with Meta-Analyses: Diagnostic Accuracy of FibroMeter Tests in Patients with Non-Alcoholic Fatty Liver Disease - Van Dijk, Anne-Marieke (J Clin Med, 2021)
Early detection of liver fibrosis is crucial to select the correct care path for patients with non-alcoholic fatty liver disease (NAFLD). Here, we systematically review the evidence on the performance of FibroMeter versions in detecting different levels of fibrosis in patients with NAFLD. We searched four databases (Medline, Embase, the Cochrane library, and Web of Science) to find studies that included adults with NAFLD and biopsy-confirmed fibrosis (F1 to F4), compared with any version of FibroMeter. Two independent researchers screened the references, collected the data, and assessed the methodological quality of the included studies. We used a bivariate logit-normal random effects model to produce meta-analyses. From 273 references, 12 studies were eligible for inclusion, encompassing data from 3425 patients. Meta-analyses of the accuracy in detecting advanced fibrosis (F ≥ 3) were conducted for FibroMeter Virus second generation (V2G), NAFLD, and vibration controlled transient elaFS3stography (VCTE). FibroMeter VCTE showed the best diagnostic accuracy in detecting advanced fibrosis (sensitivity: 83.5% (95%CI 0.58–0.94); specificity: 91.1% (95%CI 0.89–0.93)), followed by FibroMeter V2G (sensitivity: 83.1% (95%CI 0.73–0.90); specificity: 84.4% (95%CI 0.62–0.95)) and FibroMeter NAFLD (sensitivity: 71.7% (95%CI 0.63–0.79); specificity: 82.8% (95%CI 0.71–0.91)). No statistically significant differences were found between the different FibroMeter versions. FibroMeter tests showed acceptable sensitivity and specificity in detecting advanced fibrosis in patients with NAFLD, but an urge to conduct head-to-head comparison studies in patients with NAFLD of the different FibroMeter tests remains.